APLIKASI TECHNOPRENEURSHIP UNTUK MENGEMBANGKAN INDUSTRI KECIL MELALUI PENGGUNAAN TEKNOLOGI E-COMMERCE BERBASIS CONTENT MANAGEMENT SYSTEM Studi Kasus Pada UKM Mandiri Gypsum - Ahmad Muhsin (Telematika, 2014)
Central Bureau of Statistics catalog of DIY Province in the book BPS : 1102001.34 " DIYYearbook " in 2009 in the field of Industrial , Energy , and Construction said that the totalnumber of SMEs in the DIY business units with as many as 18 367 division business areasinclude : food processing , clothing and skin , chemicals and building materials , craft andgeneral , and metals and services . Data obtained through the SME Database Official webDisperindagkop obtained data for DIY types there are only 3 Gypsum SME business unit . Whilethe survey states that in some industries Gypsum Gypsum today began much-loved communitybecause it has the impression of a clean , luxurious , and provide a cool atmosphere in additionto its affordability . For that we need we need a more effective means to introduce the public toGypsum to further develop this business . UPN " Veteran " Yogyakarta is one of theacademicians who have set Technopreneurship as compulsory subjects that must be taken bystudents . Technopreneurship into a technology -based business incubator , which serves tocultivate the entrepreneurial spirit . The new breakthrough strategies to anticipate that theintellectual problem of unemployment is increasing. The difference with entrepreneurship lies inthe application of technology in entrepreneurial business processes . This study aims to applyTechnoprenurship in the real industry that serves to bridge the needs of Small IndustrialTechnology needs to help increase their business productivity . Media used in the technologypackaged e-commerce website to complete the requirements of business processes based onICT ( Information Communication Technology ) . Online stores are made in this study to applytechnology -based Information System Content Management System . E-commerce site aims toproduce a site that is automatically able to introduce a small industry online , can reach variousregions throughout the world , and capable of operating for 24 hours nonstop . TechnologyContent Management System chosen for ease of operation and ease of communicationbetween managers and consumers . The results of this study resulted in an e- commercewebsite that can be accessed in www.gypsumnatural.com , Implementation BasedTechnopreneurship Curicullum on this site to provide an alternative marketing through theInformation Technology field , provide ease of communication , and expand access to build anetworking business world.Keywords : e-commerce, Technopreneurship, Content Management System, Website